TNFSF4 Gene Variations Are Related to Early-Onset Autoimmune Thyroid Diseases and Hypothyroidism of Hashimoto’s Thyroiditis - Song, Rong-Hua (Int J Mol Sci, 2016)
The aim of the current study was to examine whether the polymorphism loci of the tumor necrosis factor superfamily member 4 (TNFSF4) gene increase the risk of susceptibility to autoimmune thyroid diseases (AITDs) in the Han Chinese population, and a case-control study was performed in a set of 1,048 AITDs patients and 909 normal healthy controls in the study. A total of four tagging single nucleotide polymorphisms (SNPs) in the TNFSF4 region, including rs7514229, rs1234313, rs16845607 and rs3850641, were genotyped using the method of ligase detection reaction. An association between GG genotype of rs3850641 in TNFSF4 gene and AITDs was found (p = 0.046). Additionally, the clinical sub-phenotype analysis revealed a significant association between GG genotype in rs7514229 and AITDs patients who were ≤18 years of age. Furthermore, rs3850641 variant allele G was in strong association with hypothyroidism in Hashimoto’s thyroiditis (HT) (p = 0.018). The polymorphisms of the TNFSF4 gene may contribute to the susceptibility to AITDs pathogenesis.